Occupations of fathers of children dying from neoplasms. Issue 4 (December 1981) - Sanders, B M; White, G C; Draper, G J
Abstract : It has been suggested in a number of recent reports that there is a possible relationship between parental occupation and malignant disease in children. A proportional mortality analysis relating deaths among children in England and Wales in 1959-63 and 1970-72 to occupation of father as stated on the child's death certificate has not shown any convincing evidence for such associations. Earlier papers published on the subject are reviewed. Although there is some slight evidence for associations between childhood tumours and certain parental occupations there is little consistency between the results reported by different authors. A previously reported association between higher social class and deaths from neoplasms was found also in this study. The explanation for this finding is unknown, and it remains possible that it is an artefact.